Threshold Effects of Dismissal Protection Legislation in Germany - Sher Verick (Institute for the Study of Labor (IZA), 2004)
In this paper we use a reform in the applicability of the Protection Against Dismissal Act or Kündigungsschutzgesetz in Germany to identify employment effects of the legislation for small establishments. Using a panel of establishments for the period 1997-2001, we find some evidence that a tightening of the threshold resulted in a higher probability of persistence and a lower probability of growth for the units in the treatment group during the post-reform years. When using the establishment size as according to the legislation, the effects were the strongest for establishments which were further away from the threshold. This result could reflect the presence of other institutional barriers or adjustment costs than those imposed by the Act. Alternatively, small establishments are unlikely to have perfect information regarding the applicability of the legislation. This is somewhat supported by the results when taking all employees as the measure for the establishment size. However, there is also some evidence that these results are being driven by other factors than the reform of the legislation.
Keywords: J23; J21; J58; 330; dismissal protection legislation; difference-in-differences; labour demand; Kündigungsschutz; Betriebsgrösse; Klein- und Mittelunternehmen; Arbeitsnachfrage; Beschäftigungseffekt; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Deutschland